Do expert reviews really drive demand? Evidence from a German car magazine - Ralf Dewenter; Ulrich Heimeshoff (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2014)
There is a wide range of magazines, newspapers, TV shows, and websites providing information on products based on product reviews or expert opinions. A natural question is, whether these reviews and expert opinions have effects on product sales. There is a small but growing literature in economics and marketing science testing the relevance of such product information, based on products such as financial instruments, wine, books and movies. However, books, movies, and wine have in common that quality is very difficult to measure. It is always also a matter of taste whether these products can be seen as high or low quality goods. Even financial products are sometimes hard to evaluate due to the well-known fact, that financial market data often contains much noise. Based on a unique dataset, we test whether test scores published in a major German car magazine have significant impact on registrations of new cars in Germany. We find that test scores for certain cars have statistically significant impact on the number of new cars sold by several leading manufacturers on the German car market.
Keywords: L15; L82; 330; Car magazines; Test Scores; Demand